2019
DOI: 10.1371/journal.pone.0217782
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sprint performance analysis in soccer: New insights from a GPS-based tracking system

Abstract: The aim of this investigation was to establish the validity of a GPS-based tracking system (Polar Team Pro System, PTPS) for estimating sprint performance and to evaluate additional diagnostic indices derived from the temporal course of the movement velocity. Thirty-four male soccer players (20 ± 4 years) performed a 20 m sprint test measured by timing gates (TG), and while wearing the PTPS. To evaluate the relevance of additional velocity-based parameters to discriminate between faster and slower athletes, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 45 publications
(52 reference statements)
1
36
1
2
Order By: Relevance
“…In agreement with previous research, it was observed in the present study that CB and CM covered the lowest distances while sprinting [5,17,35]. This is most probably due to longer running intervals of the out-lane players [35] that are associated with longer distances after the initial acceleration phase, which was shown to be around 10 meters in isolated sprinting [27].…”
Section: Physical Performancesupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous research, it was observed in the present study that CB and CM covered the lowest distances while sprinting [5,17,35]. This is most probably due to longer running intervals of the out-lane players [35] that are associated with longer distances after the initial acceleration phase, which was shown to be around 10 meters in isolated sprinting [27].…”
Section: Physical Performancesupporting
confidence: 93%
“…In order to be able to capture relevant data synchronously, wearable GPS-based tracking systems with integrated heart rate sensors are the method of choice [15] whose validity and reliability have already been proven extensively [24][25][26][27][28]. Due to the fact that wearables have only recently been approved for use in competition by FIFA, only a few studies have been published so far quantifying the position-specific physical performance and physiological demands of sub-elite soccer players with GPS and HR response [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The players’ training load during each training sessions was monitored using a Polar Team Pro sensor [ 14 ] (Polar Electro, Kempele, Finland), which simultaneously recorded spatial position (GPS) and heart rate (HR) [ 15 ]. As specified by the manufacturer, the sensor combines signals from a 10 Hz GPS with a 200 Hz sampling frequency microelectromechanical inertial measurement unit consisting of a tri-axial accelerometer, gyroscope, and magnetometer.…”
Section: Methodsmentioning
confidence: 99%
“…This technology is based on a signal concentration system of different Polar brand sensors, designed for the control and monitoring of physical activity in collective sports like soccer or basketball. This technology has been validated [ 31 , 32 ] and used in previous studies that registered the physical load of soccer tasks [ 10 , 19 ] and is currently one of the most used instruments for the quantification of the physical load in this context [ 33 ].…”
Section: Methodsmentioning
confidence: 99%